Grounds and conditions for the application of preventive measures during the pre-trial investigation of corruption criminal offenses - V. V. Romaniuk; R. I. Login (Law and Safety)
The article is devoted to clarifying the content of the grounds and conditions for the application of preventive measures during the pre-trial investigation of corruption criminal offenses. The specified scientific search was carried out taking into account the specifics of the mechanism of commission and, accordingly, investigation of the selected category of criminal offenses. The main purpose of the study is to identify and characterize the grounds and conditions for applying preventive measures during the pre-trial investigation of corruption criminal offenses. It is proved that during the pre-trial investigation of corruption criminal offenses, preventive measures are applied only if there are legal and procedural grounds. The legal basis is the existence of a reasonable suspicion that a person has committed a corruption criminal offense and risks that give the investigating judge sufficient grounds to believe that the suspect may not fulfill the procedural duties assigned to him and try to hide from the pre-trial investigation bodies, commit actions to destroy or damage evidentiary information, illegally influence other participants in the criminal proceedings, or otherwise obstruct criminal proceedings, or continue criminal illegal activities. It is emphasized that when deciding on the application of preventive measures in the category of criminal proceedings under study, it is necessary to clarify the presence of risks stipulated in Part 2 of Article 177 of the Criminal Procedure Code of Ukraine and justify their sufficiency in relation to the elements of the mechanism of committing a specific corruption criminal offense. The procedural basis is the ruling of the investigating judge at the request of the investigator, agreed with the prosecutor, or the prosecutor. If the corruption criminal offense is attributed to the jurisdiction of the High Anti-Corruption Court, then the procedural basis for applying preventive measures during the pre-trial investigation of such offenses is the ruling of the investigating judge of the High Anti-Corruption Court. Such a ruling is made at the request of the investigator, agreed with the prosecutor of the Specialized Anti-Corruption Prosecutor’s Office, or at the request of the prosecutor of the Specialized Anti-Corruption Prosecutor’s Office. When making a procedural decision, the investigating judge is obliged to take into account the conditions for applying preventive measures in criminal proceedings: the presence of evidence of circumstances indicating the presence of both components of the legal basis for applying preventive measures and the insufficiency of applying milder preventive measures to prevent the risk or risks specified in the request; ensuring the legality of restrictions on the suspect’s rights during criminal proceedings.